INTERSECTION NODE OF PREFERRED TRANSPORT MODES AND ITS MODEL CROSSING FOR CYCLISTS PARDUBICE PALACKÉHO (Perner's Contacts, 2016)
The paper is focused on specific intersection node of two types of transport – public mass passenger transport and cyclist transport. Both of these transport kinds are preferred in general way. Crossing for cyclists equipped with traffic lights located on Palackého Street in Pardubice is solved. Decelerations and stopping of a part of (urban, suburban as well as long-distance) public transport vehicles (connections) are occurred there. Operational situation is evaluated on the base of realized transport surveys. Capacity calculation of this intersection node is done next to it. Application of preference for public passenger transport in operation of traffic lights is proposed with an aim to improve the quality of operation. This proposal is evaluated by utilizing of simulation model, designed for this purpose. There are mentioned aspects for practical realisation of preference at this place as well as theoretical aspects for methods utilized for this evaluation.
Keywords: cycling; intersection node; Pardubice; model; preference; capacity; crossing for cyclists; signalling plan; simulation; traffic lights; public mass passenger transport